Development of Learning Innovation Using Augmented Reality Technology with a Learning Management System as a Learning Supplement - Apriyani, Meyti Eka; Harijanto, Budi; Hamdana, Elok Nur (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Augmented Reality technology is making significant changes in the world of education by enriching the learning experience. This article discusses the development of innovative learning by integrating Augmented Reality into the Learning Management System as a learning support. This research aims to explain the concept of incorporating Augmented Reality into a Learning Management System as a complementary approach to increasing effectiveness and engagement in learning. The integration of Augmented Reality enables the presentation of learning content in a visual and interactive form, bridging the gap between theory and practice, and increasing student motivation and understanding. The results of using Augmented Reality in learning include increased understanding of the material, higher learning motivation, and the development of practical skills. However, this article also examines the challenges that may arise, both from a technical and pedagogical perspective, during the implementation of Augmented Reality in a Learning Management System. This research provides a comprehensive view of the potential of Augmented Reality as a complement to learning in facing the changing dynamics of modern learning. This article can be a guide for educational practitioners and researchers who are interested in incorporating Augmented Reality into learning contexts in various educational environments.